Electronic Banking Utilization, Service Quality, Client Satisfaction: A Narrative Literature Review - Nazareth, John Martin; Francia, Aldon; Almogen, Marianne; Mabassa4, Eleonor (JPAIR Multidisciplinary Research, 2026)
Electronic banking has become a cornerstone of modern financial services, yet uneven adoption and persistent trust concerns continue to limit its effectiveness, particularly in emerging economies. The purpose of this study is to examine how service quality mediates the relationship between electronic banking utilization and client satisfaction, with emphasis on Philippine universal banks. Using a narrative literature review design, the study synthesizes global, ASEAN, and Philippine scholarship, integrating empirical and theoretical works grounded in the Technology Acceptance Model (TAM), SERVQUAL, and Expectancy-Disconfirmation Theory (EDT). Results of the synthesis reveal that utilization directly influences satisfaction and shapes perceptions of service quality, and that satisfaction is indirectly driven by service quality. Accessibility fosters trust and security, while frequent use enhances convenience and loyalty. The findings highlight that technological adoption alone is insufficient; satisfaction emerges when utilization is embedded within reliable, secure, and empathetic service delivery. This study contributes to scholarship by advancing an integrated mediation model, to managerial practice by emphasizing reliability and assurance in digital platforms, and to policy by underscoring the need for infrastructure investment, digital literacy, and cybersecurity frameworks. Overall, the review provides a defense-ready foundation for empirical testing and international publication.